(untitled) (Medico Legal Update, 2019)
The purpose of this study was to investigate the effect of 8-week rehabilitation exercise on active vascular health and ultimately propose an effective rehabilitation program applying various stretching methods. The research targets were females who visited hospital due to chronic diseases or metabolic syndrome; and were divided into two groups, participants of rehabilitation exercises, and non-participants of rehabilitation exercises. 10 people were included in each group. The subjects were restricted to participate in other exercise programs during the exercise period. The 8-week exercise program was designed to measure the ankle brachial index (ABI) and the cardio-ankle vascular index (CAVI) using active stretching and passive stretching. In the data processing, descriptive statistics were presented for each measurement item and a 2-way RGRM ANOVA was conducted to examine the interaction effects between groups. The results have shown significant interaction effects in ankle brachial index (ABI) and the cardio-ankle vascular index (CAVI). Therefore, the eight-week rehabilitation campaign has shown to have a positive effect on vascular health and is believed to be an effective preventive measure to reduce the incidence and risk of cardiovascular disease. Also, this rehabilitation program is thought to help prevent cardiovascular disease if it is provided to more elderly people since which does not require special places or specialized equipment.